Comprehensive National Accounting for Carbon Emissions - Geir B. Asheim; Rintaro Yamaguchi (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider the question of how to integrate carbon emissions in comprehensive national accounts for the purpose of indicating whether countries' development is sustainable. We derive an expression for national saving which includes not only the national effect of current global emissions, but also the future expected paths of emissions nationally and in the rest of the world. We illustrate how the use of our expression for national saving alters the empirical conclusions concerning the sustainability of countries, as compared to the World Bank estimates. Our calculations account for the fact that future prospects of developing countries are more affected by the global carbon emissions than they themselves affect others by their own low per capita emissions. They are thus deemed less sustainable when using our indicator. This information suggests shifting the burden of climate policies away from such countries.
Keywords: C43; D63; O47; Q01; 330; climate change; comprehensive national accounting; carbon emissions